Cost-Effectiveness of Dronedarone and Amiodarone for the Treatment of Chinese Patients With Atrial Fibrillation - Zhang, Mengran; Ren, Yu; Wang, Luying; Jia, Jianhao; Tian, Lei (Frontiers in Public Health, 2021)
Background: Atrial fibrillation (AF) is one of the most common arrhythmias in clinical practice, which brings great economic burden to patients. This study evaluated the economics of the new antiarrhythmic drug dronedarone and provides suggestions for allocation of health resources. Methods: Amiodarone was selected as the control group, and the Markov model of AF was established using nine states. The total cost and quality-adjusted life year (QALY) of dronedarone and amiodarone groups were calculated and compared. The incremental cost effectiveness ratio (ICER) value was calculated and compared with the willingness to pay (WTP) and the sensitivity analyses was conducted. Results: For China's healthcare system, the ICER of the dronedarone group compared with the amiodarone group was RMB 81,741 Yuan/QALY, which is lower than the current recommended WTP (3 times GDP per capita). Sensitivity analyses showed that the model was robust, and the drug price of dronedarone significantly impacted the results. Conclusions: Compared with amiodarone, dronedarone is more economical in the Chinese healthcare system. However, due to the lack of data on the Chinese population for some parameters, the model needs further improvement and discussion. Real-world studies on the effects of dronedarone on Chinese patients with AF would be beneficial.